Multi-objective optimization of wind-hydrogen integrated energy system with aging factor - Liu, Xinghua; Wang, Yubo; Tian, Jiaqiang; Xiao, Gaoxi; Wang, Peng (International journal of hydrogen energy, 2023)
Large-scale hydrogen production with wind power generation has been gaining increasing attention and applications. Achieving a good balance between the capacity and cost of wind power generation however remains as a critical challenge restricting the development of wind-hydrogen integrated energy systems (WHIES). In addition, the aging factor may come in over time, making negative impacts on the efficiency and cost of WHIES. In this work, a method is proposed to seek a good balance between the capacity and cost of WHIES. Specifically, by comparing operational data and equipment condition, we evaluate the aging status of the wind power generation system and the hydrogen production system, then the aging economic model of WHIES is proposed. By taking into account the actual operating conditions in constructing the WHIES objective function with the aging factor, the proposed model allows striving to maximize the production capacity with the minimum cost. An improved multi-objective gray wolf optimizer algorithm is developed to solve the WHIES cost optimization problem. Finally, case studies are carried out via MATLAB based on the configuration and experimental data for a specific wind farm located in Ningxia, China. Our results help achieve a balance between maximizing capacity and minimizing cost under various conditions. [Display omitted] •The proposed method provides operation program for different energy systems.•Cost models are used to evaluate the aging status of WHIES.•An IMOGWO is used to solve nonlinear benefit-cost coupling problems.•The balance between production and cost of WHES is discussed.